Effect of the Mediterranean diet and probiotic supplementation in the management of mild cognitive impairment: Rationale, methods, and baseline characteristics - Cardelo, Magdalena P.; Corina, Andreea; Leon-Acuña, Ana; Quintana-Navarro, Gracia M.; Alcala-Diaz, Juan F.; Rangel-Zuñiga, Oriol Alberto; Camargo, Antonio; Conde-Gavilan, Cristina; Carmona-Medialdea, Claudia; Vallejo-Casas, Juan A.; Carmona-Asenjo, Elvira; Ochoa-Sepulveda, Juan J.; et al. (Frontiers in Nutrition, 2022)
Introduction: Mild cognitive impairment (MCI) can progress to Alzheimer’s disease (AD). When MCI is not properly controlled, the speed of deterioration can dramatically increase. Reduction of oxidative stress/inflammation and the modulation of the gut-brain axis could be new potential therapeutic targets for the prevention and treatment of AD. Consumption of specific nutrients, diets and probiotic supplementation have been evaluated for neurodegenerative disorders. We focus on a detailed description of the study methods and baseline characteristics of a clinical trial aiming to evaluate the efficacy of a combined nutritional intervention, i.e., a Mediterranean diet with probiotics, on cognitive capacity in a population with MCI. Methods: In this randomized, latin-square crossover, double-blind, and controlled dietary intervention trial (clinicaltrials.gov NCT05029765), 47 MCI patients were randomized to consume three dietary interventions for 24-weeks each: 1. A Mediterranean diet supplemented with probiotics (109 colony-forming units of Lactobacillus rhamnosus and Bifidobacterium longum); 2. A Mediterranean diet + placebo; 3. A Healthy diet according to the World Health Organization (WHO) recommendations). Participants will be evaluated before and after each of the three intervention periods (each 24-weeks, with a total of 72-weeks) for adherence to the assigned diet, blood tests, cognitive performance, gut microbiota analysis and functional neuroimaging studies. Results: Fifty patients, ≥60 years-old and diagnosed with MCI, underwent randomization. A total of 47 patients completed follow-up dietary interventions (57.4% males), with a good glycemic control (HbA1c 5.88±0.09%, fasting glucose and insulin 99.7±3.3 mg/dL and 10.4±0.9 mU/L, respectively), elevated systolic blood pressure (136.9±2.1 mmHg) and increased degree of inflammation (high-sensitivity C-reactive protein, 8.83±0.87 mg/dL). Baseline adherence to the Mediterranean diet was low (7.51±0.29 points on the score that ranged from 0-14 points). Conclusions: The results of this clinical study would provide more evidence on the need for dietary therapeutic strategies, for clinical and individual practice, in the management of MCI patients to reduce the risk of AD development. Targeting lifestyle modifications in high-risk populations could prevent substantial cases of cognitive decline.